Gendered sexualities - Gagné, Patricia; Tewksbury, Richard A. (JAI, 2002)
Contemporary scholars have made important substantive and theoretical contributions to understanding the ways in which power is exercised through gender and through sexuality. Drawing upon a number of theoretical frameworks, including feminism, post-modernism, masculinities and queer theory, researchers have challenged dichotomous, static, and biologically reductionist conceptualizations of gender and sexuality. They have documented the myriad ways in which sex, gender and sexualities are far more complex than previously assumed. However, despite these advances in research, the tendency in the literature has been to examine gender or sexuality. This volume proposes a corrective to that trend by offering a collection of research based articles in which the authors examine the exercise of power at the intersection of gender and sexuality. The articles in this collection offer insights into some of the ways in which gender can be used to challenge the exercise of sexual power, as well as the ways that it can reify patriarchal, heteronormative sexual relations. Additionally, the articles advance the understanding of some of the institutionalized ways that sexual power might be used to challenge or reify gender relations. The articles in this volume have been written so that each is accessible to both students and senior scholars of gender and sexuality.
Keywords: Gender identity.; Sex.; Sex role.; Transgender people -- Identity.; Gender studies, gender groups.; Social Science -- Gender Studies.; elektronické knihy; electronic books